(untitled) (Movimenta (ISSN 1984-4298), 2023)
Introduction: Social isolation due to Covid-19 impacted the practice of physical activity and, in some cases, led to the adoption of sedentary behavior among the elderly. This fact can lead to problems such as increased pain intensity. The practice of physical activity seems to contribute to the reduction of this symptom in this population. Objective: To describe and characterize the presence of pain in elderly people who practice physical activities in the interior of Amazonas in two periods: before and during the Covid-19 pandemic. Materials and Methods: This is a longitudinal study, with a sample of 66 elderly people who practiced physical activities twice a week. Data related to pain level were collected using numerical and facial scales. For data analysis, Microsoft Office 365 and IBM/Stata MP, version 14.0, were used. Results: The results obtained in the evaluation carried out using the numerical scale demonstrate that there was a significant reduction in pain intensity (p<0.0144) during the pandemic. However, when evaluating pain intensity using the faces scale, it was not possible to observe a significant difference (p=0.9606) when comparing the two periods analyzed. Conclusion: When comparing the periods before and during the Covid-19 pandemic, it was observed that elderly people who practice physical activity, living in the interior of Amazonas, did not show an increase in pain intensity. The assessment carried out using the numerical scale demonstrated a significant decrease in this pain intensity during the pandemic.